The Design and Investigation of Teaching Evaluation Index System under the Background of Research University Construction - Chi, Qishui (RA Journal of Applied Research, 2021)
Based on the teaching characteristics of Research-oriented University, this paper designs the teaching evaluation index system of university economics and management courses. The index system includes 6 first level indexes and 31 second level indexes. We select all the graduate students in our school's business school as the survey object to study the importance of indicators at all levels in teaching evaluation. The results show that the weight of learning attitude is the highest among all the first level indicators. In all the secondary indicators, the indicators that can assess research, investigation and other related aspects generally have higher weight. These show that under the background of the construction of Research-oriented University, the traditional teaching mode of instilling knowledge into students by teachers can no longer meet the needs of the development of the times. The education in the new era should transform to the research-oriented teaching mode which mainly cultivates students' research and analysis ability.